More on dual actions for massive spin-2 particles - Dalmazi, D. [UNESP]; Santos, A. L. R. dos (Iop Publishing Ltd, 2020)
Here we start from a dual version of Vasiliev's first order action for massless spin-2 particles (linearized first order Einstein-Hilbert) and derive, via Kaluza-Klein dimensional reduction fromD+ 1 toDdimensions, a set of dual massive spin-2 models. This set includes the massive 'BR' model, a spin-2 analogue of the spin-1 Cremmer-Scherk model. In our approach the linearized Riemann curvature emerges from a solution of a functional constraint. InD= 2 + 1 the BR model can be written as a linearized version of a new bimetric model for massive gravitons. We also have a new massive spin-2 model, in arbitrary dimensions, invariant under linearized diffeomorphisms. It is given in terms of a non symmetric rank-2 tensor and a mixed symmetry tensor.
Keywords: spin-2; duality; massive gravity; Fierz-Pauli